THE EFFECT OF INCLUSIVE TEAM, AGILE LEADERSHIP, AND ORGANIZATIONAL AGILITY ON ORGANIZATIONAL PERFORMANCE: A Literature Review in a Communication Company - Budi Susanto; Wahyu Wiguna; Martinus Tukiran (International Journal of Economy, Education and Entrepreneurship, 2023)
Many factors influence organizational performance, one of which is the influence of HR management. Inclusive teams, agile leadership, and organizational agility affect organizational performance. This study aimed to see how inclusive teams, agile leadership, and organizational agility affect organizational performance. Although the methods used are qualitative studies, literature studies, literature research, and literature reviews. The results show that several journals influence organizational performance. These results become a recommendation for communication companies to improve organizational performance